Post-merger and Acquisition Integration: A Case Review of Dial Henkel And BP Amoco - Lufina Mahadewi (International Journal of Business Studies, 2018)
Post-merger and Acquisition (M&A) integration often deals with significant transformational changes of merging companies in terms of development, communication, implementation and harmonization of a new shared vision, strategic objective, corporate culture, and also combination of best companies’ value practices. The transformational change is accentuated on facilitating the role of developing and executing an effective post-M&A Integration to build change cohesively with the strategic management of M&A, and also in terms of removing barriers to the success of M&A transaction. The aims of this study are to give a clear and deep understanding on how to manage the soft factors issues that address in M&A process especially in the post-M&A integration process and also to elucidate the critical success factor of M&A process by instilling the best characteristics and the effectiveness level of leadership aspect in M&A. The methodology used in this research is descriptive qualitative research with a method or approach of a case study of Henkel’s Acquisition of The Dial Corporation in 2004. The acquisition of a USA company Dial by a German company Henkel evidenced that both companies were successful in M&A transaction and employed the effectiveness of multi-culture integration strategy. Another case study used in this research is British Petroleum (BP) and American Oil Company (Amoco) (also Atlantic Richield Company (ARCO) and Burmah Castrol) in 1998-2000. The case of BP Amoco showed that the monoculture integration strategy or cultural imposition can also lead to a value creation. Both case studies showed that successful integration requires leadership as a foundation to build a solid execution of post-M&A integration projects in how they planned, communicated and delivered the objectives of the projects.